Preventing crime and disorder in public places: blending opportunity reduction, guardianship and welfare - Prenzler, Tim (Crime prevention and security management, 2024)
This accessible, short book provides scientifically informed guidance on effective and holistic place management strategies for preventing crime. It integrates theoretical perspectives and practical examples of crime prevention methods that can be readily implemented by responsible stakeholders. It covers locations including town centers, shopping malls, parks, beaches, transit hubs, campuses, stadiums and entertainment precincts, where security programs sometimes attract criticism regarding the exclusion or persecution of marginalized groups. This book advocates for overlapping forms of crime prevention and social support that address the need to make large improvements in safety in public places while supporting marginalized and vulnerable groups. Readers are exposed to a wide range of successful case studies as well as the central role of a systematic problem-solving methodology. It speaks to crime prevention and social services professionals, academics, and students, as well as interested members of the public. Tim Prenzler is Professor of Criminology in the School of Law and Society at the University of the Sunshine Coast (USC), Australia. He was the foundation Coordinator of the Bachelor of Criminology and Justice from 2015 to 2018. He teaches courses in policing, crime prevention, and criminal justice ethics and accountability.